Management of Orthopaedic Emergencies During a Pandemic: Compartment Syndrome of the Hand in a Patient with COVID-19: A Case Report. Issue 3 (15th July 2020) - Hill, Kelly L.; Wu, Victor J.; Kusumoto, Hirofumi; Sherman, William F.; Savoie, Felix H.
Abstract : Case: A 58-year-old man presented with acute respiratory distress syndrome and coagulopathy secondary to COVID-19. He developed acute compartment syndrome (ACS) of the left hand. He underwent a bedside 10-compartment decompression of the hand with volar forearm and carpal tunnel release while in the ICU. This report adds to the scarce body of literature regarding orthopaedic complications related to COVID-19. Conclusion: Coagulopathy secondary to COVID-19 can be a risk factor for the development of ACS. Frequent examinations of lines, restraints, and extremities are recommended. The COVID-19 pandemic presents unique challenges, necessitating clinical adjustments to best care for patients.